Women at War : the Story of Fifty Military Nurses Who Served in Vietnam. (Studies in health, illness, and caregiving., 1990)
Norman tells the dramatic story of fifty women-members of the Army, Navy, and Air Force Nurse Corps-who went to war, working in military hospitals, aboard ships, and with air evacuation squadrons during the Vietnam War. Here, in a moving narrative, the women talk about why they went to war, the experiences they had while they were there, and how war affected them physically, emotionally, and spiritually.